ARTISTIC AND SUBSTANTIVE EVOCATION OF FOLK TRADITIONS IN THE UKRAINIAN THEATER AT THE BEGINNING OF THE XX CENTURY (BASED ON THE MATERIALS OF THE "NEW ART" JOURNAL) - Рибченко, О. Г. (Art and Design, 2021)
The purpose to demonstrate the implementation of folk traditions in the 1920s scenography on the example of two theatrical performances: “Sava Chaly” (Theatre “Berezil,” Kharkiv, 1927) and “The Fair at Sorochyntsi” (State Ukrainian Opera, Kyiv, 1925) based on the materials of the archival editions of the “New Art” journal (Kharkiv, 1925–1928). Methodology. The methodological basis of the study is a systematic approach, methods of synthesis, generalization, comparative historical and art history analysis. Results. The review of the archival issues of the weekly “New Art” journal allowed to confirm that folk traditions played a prominent role in theatre art at the beginning of the XX century and served as a source of inspiration for scenographers, composers, performers etc. The study indicates the importance of the “New Art” journal as a primary source of information on the cultural events in Ukraine. Based on its issues, the study analyses the publications and photo materials on the scenography of the “Sava Chaly” (Theatre “Berezil,” Kharkiv, 1927) and “The Fair at Sorochyntsi” (State Ukrainian Opera, Kyiv, 1925) performances. The elements of Ukrainian folk art in these performances were emphasised. It is noted that evocation of the folk traditions in the scenography was both a showcase and a guarantee of the preservation of the ethnocultural phenomena in the theatrical environment of the period. The novelty of the study is the identification of the specifics of the use of folk traditions and ethnic elements in the scenography of the 1920s, as well as the introduction into the scientific discourse of the “New Art” journal's issues, which offer materials on the implementation of the folk traditions by directors, stage designers and performers. The practical significance. The study can be useful for research of the history of Ukrainian scenography; the analysis of the artistic heritage of stage designers of the XX century's leading theatres is vital for enriching the modern Ukrainian stage design.